Pendampingan Penerapan Sustainable Packaging Untuk Produk Jajanan Rena Snack - Widyastuti Widyastuti; Ida Betanursanti; Alifta Dicasani; R. Hartini Natang (Publikasi Indonesia, 2025)
The use of plastic as a packaging material remains the primary choice among Micro, Small, and Medium Enterprises (MSMEs) due to its practicality and affordability. However, growing environmental awareness has encouraged the adoption of sustainable packaging as a more ecologically responsible alternative. This activity aimed to assist Rena Snack in identifying and applying environmentally friendly packaging alternatives suited to the characteristics of its products. The program was implemented in three stages: preparation, implementation, and monitoring and evaluation. The results showed that sustainable packaging was relatively easy to implement, effectively maintained product quality during distribution, and remained cost-efficient. However, several challenges emerged, including mismatched packaging sizes, limited resistance of paper materials to oil and moisture, and extended processing times when using banana leaves. The sustainability evaluation indicated that the combination of paper and banana leaves held promising potential for broader application, provided there were adjustments to production efficiency and alignment with consumer preferences. This initiative is expected to encourage broader adoption of sustainable packaging practices among MSMEs to enhance competitiveness in the green economy era.